Introduction to audiovisual archives - Stockinger, Peter (ISTE., 2012)
Today, audiovisual archives and libraries have become very popular especially in the field of collecting, preserving and transmitting cultural heritage. However, the data from these archives or libraries - videos, images, sound tracks, etc. - constitute as such only potential cognitive resources for a given public (or "target community"). They have to undergo more or less significant qualitative transformations in order to become user- or community-relevant intellectual goods. These qualitative transformations are performed through a series of concrete operations such as: audiovisual text s